2013
DOI: 10.15358/0344-1369_2013_2_91
|View full text |Cite
|
Sign up to set email alerts
|

Value Creation for Luxury Brands through Brand Extensions: An Investigation of Forward and Reciprocal Effects

Abstract: Luxury brands such as Louis Vuitton, Gucci, or Chanel regularly expand beyond their core business and nowadays offer a wide range of products including accessories, perfumes, watches or jewelry, and even services. The use of brand extensions has become central to the business model of most luxury brands. While research on brand extensions for nonluxury brands has produced many insights into the process of brand extension evaluation from a consumer point of view, surprisingly little research has addressed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This study focuses on this broad meaning of luxury goods and not just focusing on luxury fashion like the majority of previous studies. Traditional luxury fashion brands such as Armani have seen an opportunity in other forms of luxury goods such as restaurants, bars, furniture and chocolate and expanded to these sectors capitalizing on their strong brand equity Versace and Bulgari are few of the luxury brands that have entered the hotel business (Albrecht et al, 2013).…”
Section: Luxury and Luxury Goodsmentioning
confidence: 99%
“…This study focuses on this broad meaning of luxury goods and not just focusing on luxury fashion like the majority of previous studies. Traditional luxury fashion brands such as Armani have seen an opportunity in other forms of luxury goods such as restaurants, bars, furniture and chocolate and expanded to these sectors capitalizing on their strong brand equity Versace and Bulgari are few of the luxury brands that have entered the hotel business (Albrecht et al, 2013).…”
Section: Luxury and Luxury Goodsmentioning
confidence: 99%
“…These findings have to be interpreted in the context of the brands used in the survey: Given that three of the brands that have been utilized as experimental stimuli are nonluxury brands, it does not seem surprising that the value dimensions associated to luxury brands-on averagedo not emerge as important determinants of extension evaluation. In this context, a recent study by Albrecht, Backhaus, Gurzki, and Woisetschläger (2013) has shown that prestige value seems to play a major role when focusing on brand extendibility in the pure case of luxury brands.…”
Section: Discussion Implications and Future Researchmentioning
confidence: 99%
“…However, research has generally paid less attention to emotions as a psychological force that leads to luxury consumption (Makkar & Yap, 2018). Of the studies that have considered them, Zhang and Zhao (2019) demonstrated the emotional value of luxury fashion goods in significantly enhancing Chinese consumers’ purchase intention, while the experience of emotional arousal toward a luxury brand has been found to be a significant predictor of brand success (Albrecht et al, 2013). Thus, the current research hypothesized that:…”
Section: Review Of the Relevant Literature And Hypothesis Developmentmentioning
confidence: 99%